2003
DOI: 10.1073/pnas.0630422100
|View full text |Cite
|
Sign up to set email alerts
|

Transcription termination control of the S box system: Direct measurement of S -adenosylmethionine by the leader RNA

Abstract: Modulation of the structure of a leader RNA to control formation of an intrinsic termination signal is a common mechanism for regulation of gene expression in bacteria. Expression of the S box genes in Gram-positive organisms is induced in response to limitation for methionine. We previously postulated that methionine availability is monitored by binding of a regulatory factor to the leader RNA and suggested that methionine or S-adenosylmethionine (SAM) could serve as the metabolic signal. In this study, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
238
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(257 citation statements)
references
References 26 publications
13
238
0
2
Order By: Relevance
“…Increased levels both of MetR and homocysteine would presumably also occur in both MetJand MetK-deficient cells, both of which are induced for metA, B and C with or without in vivo SAMase activity. These and other conflicting and unresolved possibilities surrounding SAMase-mediated induced met gene induction can only be resolved by further investigation of the role of MetR activity and/or homocysteine levels, or by searching for other unidentified regulatory elements that influence met gene activity such as revealed by the role of SAM in the S-box system of Bacillus subtilis (Murphy McDaniel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels both of MetR and homocysteine would presumably also occur in both MetJand MetK-deficient cells, both of which are induced for metA, B and C with or without in vivo SAMase activity. These and other conflicting and unresolved possibilities surrounding SAMase-mediated induced met gene induction can only be resolved by further investigation of the role of MetR activity and/or homocysteine levels, or by searching for other unidentified regulatory elements that influence met gene activity such as revealed by the role of SAM in the S-box system of Bacillus subtilis (Murphy McDaniel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Four different aptamer classes recognizing Sadenosylmethionine (AdoMet or SAM) have been identified to date. SAM-I or S-box (Epshtein et al 2003;McDaniel et al 2003;Winkler et al 2003), SAM-II (Corbino et al 2005), SAM-III or SMKbox (Fuchs et al 2006), and SAM-IV ) often regulate the same genes in different organisms (e.g., SAM synthase, homoserine O-succinyltransferase). The discovery of a second natural preQ 1 aptamer class shows that SAM is not a special case and that additional metabolites may be bound by multiple distinct RNA architectures to control similar sets of genes in different organisms.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,24,36 The large diversity of SAM riboswitches likely reflects the importance of regulating SAM-related metabolic pathways. 3 SAM riboswitches exhibit very high affinity for SAM and strongly discriminate against SAM-related analogs such as S-adenosylhomocysteine (SAH), 33,34 which differs from SAM by the absence of a single methyl group and the associated positive charge on the sulfur atom. A study has reported the existence of SAH-sensing riboswitches, 37 indicating that SAM/SAH riboswitches exploit chemical differences between closelyrelated metabolites to prevent cellular misregulation, which is consistent with recently obtained crystal structures.…”
Section: S-adenosylmethionine (Sam) Riboswitchesmentioning
confidence: 99%
“…11,[30][31][32][33][34] These riboswitches are located upstream of genes involved in the metabolism, biosynthesis and transport of methionine or SAM. 11,35 The SAM riboswitch class is one of the most abundant, 36 especially in Gram-positive organisms, and is unique in that six distinct SAM riboswitch families have been reported to date that bind SAM in diverse ways.…”
Section: S-adenosylmethionine (Sam) Riboswitchesmentioning
confidence: 99%